Comparison of bone mineral density according to domains of sedentary behavior in children and adolescents - Christofaro, Diego Giulliano Destro [UNESP]; Tebar, William Rodrigues [UNESP]; Saraiva, Bruna Thamyres Ciccotti [UNESP]; da Silva, Gabriela Caroline Rodrigues [UNESP]; dos Santos, Amanda Barbosa [UNESP]; Mielke, Gregore Iven; Ritti-Dias, Raphael Mendes; Mota, Jorge (Springer Nature, 2022)
Background: Somatic maturation and the age at onset of puberty are closely related to bone mineral density (BMD), and are potential confounders of the associations between physical activity, sedentary behavior (SB) and BMD in adolescents. Thus the aim was compare BMD at different anatomical sites according to different domains of SB. Methods: The sample consisted of 88 young people (54 boys and 34 girls; 9.5 ± 1.5 years). The self-reported SB was measured by the time spent on TV, computer, video game and smartphone. BMD at each location and throughout the body was assessed by DEXA. Physical activity was assessed by a questionnaire. The comparison of the different types of BMD sites according to the SB levels for each screen device and the total SB were analyzed by Covariance Analysis (ANCOVA). Results: Whole-body BMD was higher in young people with low total SB (Total BMD = 0.957 ± 0.042) than in those with moderate (Total BMD = 0.921 ± 0.053) and high SB (Total BMD = 0.929 ± 0.051) (p-value = 0.011). Children and adolescents with low total SB had higher BMD legs (0.965 ± 0.056) than young people with high total SB (BMD legs = 0.877 ± 0.209), but this relationship was attenuated when the analyzes were adjusted for physical activity (p-value = 0.068). Conclusion: Adolescents with high sedentary behavior tend to have lower whole body bone mineral density than those with low sedentary behavior.
Keywords: Adolescent; Bone density; Child; Health; Sedentary